First report of root rot of hydroponically grown peppermint (Mentha × piperita) caused by a Pythium myriotylum in Cyprus - Pantelides, Iakovos S.; Tsolakidou, Maria Dimitra; Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2017)
In June 2016, almost half of the peppermint (Mentha piperita) plants (64 in total) grown hydroponically suffered from severe root rot in Cyprus. Initial symptoms included brown to dark brown lesions on the roots that gradually enlarged and eventually caused rotting of the entire root system. In advanced stages, the plants showed severe stunting and poor growth while the older leaves became yellow and necrotic. The causal pathogen was identified as Pythium myriotylum based on morphological, molecular and pathogenicity analyses. This is thought to be the first report of P. myriotylum causing root rot of hydroponically grown peppermint in Cyprus and worldwide.
Keywords: Pythium; Oospore; Damping Off Disease